Penetapan Total Flavonoid, Aktivitas Antioksidan dan Karakterisasi Nanopartikel Ekstrak Etanol Daun Kelor (Moringa pterygosperma Gaertn.) - Tinta Julianawati; Hendy Hendarto; Widjiati Widjiati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Moringa pterygosperma is one of the plants in Indonesia that is often used in herbal medicine. Moringa leaves contain many phytochemical compounds, one of the compounds is flavonoids which function as antioxidants. Flavonoid compounds in vitro can inhibit lipid peroxidation by breaking the chain of peroxyl radicals. Moringa leaf benefits in the field of herbal medicine are formed with a variety of preparations. One of the preparations is in the form of extracts with the aim of attracting chemical components to natural materials The extraction process has a disadvantage because the level of solubility in water is still low. The nanoparticle technique is a strategy to increase the bioavalbicibility of herbal active compounds. This research was experimental in order to determine the total flavonoid levels contained in Moringa leaf extract. In addition, it was also to find out the antioxidant activity and particle size of the moringa leaf extract nanoparticles. Determination of flavonoid levels using spectrophotometric methods. The antioxidant activity of moringa leaf extract nanoparticles was tested using the DPPH method (2,2-diphenyl-picrylhdrazyl) and to determine the particle size used by using the Particle Size Analyzer (PSA). The results of the study showed total flavonoid levels in moringa leaf extract (1.97 ± 1.07)%. Antioxidant activity of 451.8 ppm with a reduction of 2.8% and particle size in the moringa leaf extract nanoparticles of ± 134.78 nm. Moringa leaf extract nanoparticles include low antioxidants. Keywords: moringa; nanoparticles; antioxidants